1977
DOI: 10.1007/bf01263028
|View full text |Cite
|
Sign up to set email alerts
|

Einflu� der molkereitechnischen Behandlung der Rohmilch auf den Aflatoxin-M1 Gehalt der daraus hergestellten Produkte

Abstract: Several contracdictory results in the literature lead us to the conclusion, that the influence of raw milk processing on aflatoxin content should be tested under as close as possible practical conditions. Even though storage at 5 degrees C for 1-3 days does not greatly influence aflatoxin content (11-25% reduction), this might still be important for food inspection. Although experiments on exposure to light resp. oxygen were repeated ten times, the results could not be definitely be shown as due to oxidation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
3

Year Published

1978
1978
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 14 publications
2
10
0
3
Order By: Relevance
“…These results are in agreement with those of El-Deep, Zaki, Shoukry, and Kheadry (1992), who found 9.5% and 26% decreases in AFM1 after the heat treatment at 63°C for 30 min and at 121°C for 15 min, respectively, while Kiermeier and Mashaley (1977), reported that various heat-time treatments caused reductions in the AFM1 concentrations of milks between 12% and 40%. Recently, Choudhary, Sharma, and Borkartria (1998) studied the eVect of various heat-treatments on AFM1 content of cow's milk and reported that sterilization of milk at 121°C for 15 min caused 12.21% degradation of AFM1, whereas boiling decreased AFM1 by 14.50%.…”
Section: Resultssupporting
confidence: 94%
“…These results are in agreement with those of El-Deep, Zaki, Shoukry, and Kheadry (1992), who found 9.5% and 26% decreases in AFM1 after the heat treatment at 63°C for 30 min and at 121°C for 15 min, respectively, while Kiermeier and Mashaley (1977), reported that various heat-time treatments caused reductions in the AFM1 concentrations of milks between 12% and 40%. Recently, Choudhary, Sharma, and Borkartria (1998) studied the eVect of various heat-treatments on AFM1 content of cow's milk and reported that sterilization of milk at 121°C for 15 min caused 12.21% degradation of AFM1, whereas boiling decreased AFM1 by 14.50%.…”
Section: Resultssupporting
confidence: 94%
“…Mc Kinney et coll. (1977) observent une disparition de 40 % ou de 80 % de l'AFM1 initiale après un stockage, respectivement, de 4 ou de 6 jours à 00 C. De même, Kiermeier et Mashaley (1977) observent une baisse de 11 à 25 % du taux de l'AFMI, après 1 à 3 jours d'entreposage à 50 C. Cependant, Stoloff et coll. (1975) notent une stabilité du taux de cette toxine dans le lait après 17 jours à 4 0 C.…”
Section: • Effet De La Réfrigérationunclassified
“…1983;Grant et Carlson, 1971 ;Kiermeier et Mashaley, 1977 ;Stoloff et coll., 1975). Dans le cas d'un lait naturellement contaminé, 84 % de l'AFM1 initiale se retrouve dans le lait écrémé, cette proportion étant de 75 à 94,5 % pour un lait artificiellement contaminé (Blanc et coll., 1983;Grant et Carlson, 1971 ;Kiermeier et Mashaley, 1977).…”
Section: • Effet De La Pasteurisationunclassified
See 1 more Smart Citation
“…Since milk may be processed in numerous ways, the effects of storage and processing on stability and distribution of AFM 1 are of great concern. Kiermier and meshaley (1977) reported the effect of cold treatments. They observed that detectable AFM 1 decreased by 11 to 25% after 3 days at 5ºC, 40% after 4 days at 0ºC, and 80% after 6 days at 0ºC.…”
Section: Regionmentioning
confidence: 99%